Pengaruh Penggunaan Tepung Kulit Pisang Terhadap Mutu Organoleptik Kue Donut - A. Khairun Mutia; Deysi Pakaya (Agropolitan, 2016)
Banana peels is one type of by-product rich environment. Banana peels generally untapped, just dumped as waste or used as organic livestock feed such as goats, cows and Buffalo. Waste banana peels contain high nutrients mainly on vitamins and vast grounds so that it can be utilized as raw food way processed into flour. One of a kind then the food that can be made from flour banana peels is a cake donut. The aim of this research is to know the best formulation of the concentration of flour wheat flour and banana peels the best of organoleptic. Characteristic of product analyzed organoleptic test and nutrient composition measurement include content of protein, water, ash conten and carbohydrat. Formulation of flour wheat flour and banana peels are favored by panelists was flour banana skin as much as 75% and wheat flour as much as 25%. Values test nutrient content of a product is best to water content 17.52% ash content was 1.14%, and carbohydrate content was 18.52% and protein content was 17, 23%.